The 2020 EFQM Model digital transformation: Νew features and Assessors' view - Deliou, Cleopatra; Koemtzi, Maria (International Conference on Business and Economics - Hellenic Open University, 2023)
Background: The EFQM Model, the most widely applied Business Excellence Model in Europe, can be used by any type of organization in order to conduct a thorough analysis of its strengths and its areas for improvement. The model can be used in two ways: both as a diagnostic tool for self-assessment and as a model for management control. Purpose: The main objective of this paper is to identify and analyze the modifications introduced to the latest version of the EFQM Model (version 2020). In an attempt to depict the main elements of the revised version, a comparison is made between the last and the previous version of the model aiming to identify the key features that need to be considered by applicant organizations when they decide to fulfill the model’s new requirements. Methodology: A literature review is conducted in order to illustrate the evolution of the model to date and a comparative analysis is used as a key research method for studying the differences between the last two versions of the model. The research is supported by interviewing Certified Assessors of the EFQM Model who have already got trained in the new features of the latest version. Findings: The 2020 version allows organizations and individuals to embrace change, drive performance and evolve for the future. The creation of the Assess Base has replaced the previous paper – driven process and it brought the assessment process a step closer to digitalization for both EFQM members and Assessors. Research Limitation: The latest version of the EFQM Model 2020 is very new and the knowledge related to its use is very limited. Therefore, the findings of this paper are mainly driven by the Assessors’ knowledge and involvement with little possibility to question or confirm the points extracted from them. Originality/ value: This paper is the first attempt to compare the last two versions of the EFQM Model. By illustrating the new key features introduced to the model, this paper may form the basis for further research on the benefits gained by the use of these features. EL classification: Μ19 Keywords: EFQM model, 2020 version, comparative data, stakeholders